A leadership-based framework for improving Saudi Arabian female participation in sports - Alruwaili, Mamdouh Dawish (Frontiers in Sports and Active Living, 2023)
Study purpose: to analyze the relationship between the leadership styles and sports engagement among female sport persons in Saudi Arabia and proposes a framework model for improving Saudi Arabian female participation in sports. Methods: This study adopted an online cross-sectional survey design for achieving the research aim. Survey instruments included multi-factor leadership questionnaire (MLQ) and Utrecht Work Engagement Scale (UWES). The study participants included adult female sports persons from various sports clubs in Saudi Arabia. A total of 329 responses were received, out of which 35 were incomplete; therefore, a total of 294 responses were considered for the data analysis. Results: Transformational leadership style was identified to be the most preferred style compared to transactional and laissez-fare leadership styles. Older participants (>25 years) perceived transformational leadership scales including inspirational motivation, intellectual stimulation, and individual consideration to be more effective (p < .05) compared to younger participants. Transformational leadership has strong positive correlation with all engagement scales (as correlation coefficient 'r' was greater than 0.7, p < .01).Conclusion: Inspirational motivation could be an effective approach in increasing the female participation in Saudi Arabia, as they are mentally unprepared due to the experience of sociocultural restrictions for decades.